12 Understanding factors in the development of stent thrombosis: results from a large UK cohort study. (24th April 2016) - Malik, Nikesh; Shah, CM; Goodall, AH; Gershlick, AH
Abstract : Introduction: Despite advances in stent technology, stent thrombosis (ST) remains a significant complication of PCI. Mechanisms are multi-factorial and poorly understood. Methods: As part of the European multi-centre PRESTIGE project, we established a ST study, collecting data from patients with definite ST at 12 UK sites from April 2012 to October 2014. Demographic and clinical data were collected and angiographic images analysed. Intracoronary thrombus was examined histopathologically and OCT done when possible. We performed platelet function testing (PFT) at 3 time points and took blood for thrombin generation and DNA analysis. All non-invasive studies were also done in a mean of 2.6 matched controls per ST case. Results: 138 patients with definite ST and 353 controls were recruited in the UK. Of the ST cases, 23% were early, 8.7% late and 68.1% very late after the initial PCI. A summary of the OCT findings is shown in Figure 1 . Demographics, clinical data, PFT and thrombin generation results will be presented. Conclusions: Using a multi-centre approach, we collected multi-source data from patients with coronary ST and matched controls. PFT data, thrombin generation and OCT pullbacks have been analysed to identify important risk factors and to validate strategies to reduce the risk of ST. We are able to establish a profile of potential ST cases, potentially identifying those at high risk.